Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.tins.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The CHRNA5–A3–B4 Gene Cluster and Smoking: From Discovery to Therapeutics

Abstract: Genome-wide association studies (GWASs) have identified associations between the CHRNA5–CHRNA3–CHRNB4 gene cluster and smoking heaviness and nicotine dependence. Studies in rodents have described the anatomical localisation and function of the nicotinic acetylcholine receptors (nAChRs) formed by the subunits encoded by this gene cluster. Further investigations that complemented these studies highlighted the variability of individuals’ smoking behaviours and their ability to adjust nicotine intake. GWASs of smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 56 publications
5
57
0
Order By: Relevance
“…To conclude, the present study provides multiple-level, yet preliminary evidence that, in people at high-risk for severe smoking outcomes, gene variants from the nicotinic pathway may further moderate the risk for specific tobacco smoking phenotypes. Associations showed both a polygenic and a pleiotropic nature that included SNP x SNP interactions, in line with previous research in less specific populations [14]. Taken altogether, our findings also highlight the importance of metabolic and chaperone/trafficking proteins in the pathogenicity of nAChRs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…To conclude, the present study provides multiple-level, yet preliminary evidence that, in people at high-risk for severe smoking outcomes, gene variants from the nicotinic pathway may further moderate the risk for specific tobacco smoking phenotypes. Associations showed both a polygenic and a pleiotropic nature that included SNP x SNP interactions, in line with previous research in less specific populations [14]. Taken altogether, our findings also highlight the importance of metabolic and chaperone/trafficking proteins in the pathogenicity of nAChRs.…”
Section: Discussionsupporting
confidence: 91%
“…The present study replicated the previously identified associations between CHRNA3 and smoking behaviours, including the number of CPD, which typically involved rs1051730 [14], a plausible tag marker for functional haplotypes in the CHRNA5-A3-B4 cluster. This makes rs8040868 a relatively new SNP of interest in the cluster.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A recent survey by counted a total of 287 human genetics studies on nicotine dependence, including 242 candidate gene association, 22 genome-wide linkage, 18 GWAS, and five targeted sequencing studies. We refer readers to existing reviews for detailed findings (Greenbaum & Lerer, 2009;Wang & Li, 2009;Lassi et al, 2016;Wen et al, 2016). In brief, several neurotransmitter systems, such as the acetylcholinergic, dopaminergic, GABAergic, and glutamatergic systems, have been implicated.…”
Section: Human Genetic Studiesmentioning
confidence: 99%
“…The vMHb/IP pathway is also of interest due to its expression of unusual acetylcholine receptor subunits, including the channel‐forming α3 and β4 receptor subunits in the vMHb, and the “accessory” α5 receptor subunit expressed in the IP subnuclei that receive vMHb input (Hsu et al, ; Marks et al, ; Salas et al, ). These nicotinic receptors are of special interest because the genes encoding the α5/α3/β4 subunits are colocated in the mouse and human genomes, and in humans, alleles at this locus, including a functional variant in the α5 receptor, have been associated with smoking behavior (Berrettini & Doyle, ; Lassi et al, ).…”
Section: Introductionmentioning
confidence: 99%